Contribution of potassium solubilizing bacteria in improved potassium assimilation and cytosolic K+/Na+ ratio in rice (Oryza sativa L.) under saline-sodic conditions - Nawaz, Aniqa; Qamar, Zia Ul; Marghoob, Muhammad Usama; Imtiaz, Muhammad; Imran, Asma; Mubeen, Fathia (Frontiers in Microbiology, 2023)
Sodium-induced potassium (K+) deficiency is more prevalent in salt-affected soils. Plants experience K+ starvation thus cytosolic K+/Na+ ratio is lowered, which is a prerequisite for their survival. K+ enrichment in crops can be acquired via K-solubilizing bacteria as a sustainable green agriculture approach. This study was conducted to explore potent K-solubilizing bacteria from the rhizosphere of wheat, rice, and native flora grown in salt-affected soils in two distinct regions of Pakistan. The aim of this work was to evaluate the contribution of microbial consortiums to the improvement of K+ assimilation and cytosolic K+/Na+ ratios in rice crops under saline-sodic conditions. Among 250 bacterial isolates, 9 were selected based on their salt (11% NaCl) and alkali (9) tolerance and K-solubilization indices (1.57–5.67). These bacterial strains were characterized for their plant growth-promoting traits and identified based on 16S rRNA gene sequencing. A consortium of five strains, namely, Enterobacter hormaechei, Citrobacter braakii, Pseudomonas putida, Erwinia iniecta, and Pantoea agglomerans, was used as a bio-inoculant to evaluate its role in K+ assimilation, cytosolic K+/Na+ ratio, and subsequent yield enhancement in rice grown under saline-sodic conditions. The impact of applied consortium on rice was assessed under variable salt levels (Control, 40, 80, and 120 mM) in a pot experiment and under natural saline-sodic conditions in the field. Plant agronomical parameters were significantly higher in the bacterial consortium-treated plants, with a concomitant increase in K+-uptake in root and shoot (0.56 and 0.35 mg g−1 dry wt.) of the salt-tolerant rice variety Shaheen. The root K+/Na+ ratio was significantly improved (200% in 40 mM and 126% in 80 mM NaCl) and in the shoot (99% in 40 mM and 131% in 80 mM) too. A similar significant increase was also observed in the salt-susceptible variety Kainat. Moreover, grain yield (30.39 g/1,000 grains wt.) and biomass (8.75 g) of the rice variety Shaheen, grown in field conditions, were also improved. It can be concluded that K-solubilizing bacteria can be used as bio-inoculants, contributing to growth and yield increment via enhanced K-assimilation and cytosolic K+/Na+ ratio in rice crops under salt stress.